Does rotavirus vaccination reduce deaths from diarrheal illness in infants?. Issue 2 (February 2017) - Garcia, Michelle; Pisculli, Jenny
Abstract : EVIDENCE‐BASED ANSWER : Rotavirus immunization does not appear to decrease mortality (SOR: B, single RCT), however, it does decrease any rotavirus gastroenteritis (RG), severe gastroenteritis, and very severe gastroenteritis (SOR: A, RCTs).